2020
DOI: 10.5603/cj.a2018.0067
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic predictors of atrial fibrillation recurrence after catheter ablation: A literature review

Abstract: Background: Catheter ablation (CA) is a well-known treatment option for patients with symptomatic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 47 publications
1
29
0
2
Order By: Relevance
“…In line with previous results (29), LVEDD was higher in the recurrence group compared to the non-recurrence one, which reflects diastolic dysfunction and impaired LVEF, both observed in AF recurrence. Averaged decreased TAPSE as well as impaired right ventricular function could be found more commonly in the recurrence group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous results (29), LVEDD was higher in the recurrence group compared to the non-recurrence one, which reflects diastolic dysfunction and impaired LVEF, both observed in AF recurrence. Averaged decreased TAPSE as well as impaired right ventricular function could be found more commonly in the recurrence group.…”
Section: Discussionsupporting
confidence: 92%
“…Assessing diastolic function has revealed significantly impaired diastolic function in the recurrence group, giving another pathophysiological hint for LA enlargement and AF recurrence (29).…”
Section: Discussionmentioning
confidence: 99%
“…19 A few echocardiographic parameters have been evaluated as predictors of AF recurrence. In a literature review by Lizewska-Springer et al, 21 full-text articles were analysed and a few features were outlined. 20 Left atrial diameter, right atrial size, right atrial volume index, left ventricle ejection fraction, and diastolic dysfunction carried significant preprocedural prognostic value and outlined the following cut-off values as predictors of AF recurrence after CA:LA diameter >50-55 mm or left atrial volume indexed to body surface area >34 ml/m 2 , E/é >13-15, LA strain assessed by speckle-tracking electrocardiography <20-25% and total atrial conduction time measured by tissue Doppler imaging >150 ms.…”
Section: Predictors Of Recurrencementioning
confidence: 99%
“…A systematic review by Balk et al on the predictors of AF recurrence after radiofrequency CA synthesises the data reported in 2,169 different citations, focusing their attention on the significant preprocedural patient characteristics, such as AF type, AF duration, left atrial diameter, left ventricular ejection fraction, sex, age, the presence of structural heart disease and the presence of hypertension. 21 Their meta-analysis showed that not one of these clinical parameters is able to predict arrhythmia recurrences at a high level of evidence.…”
Section: Predictors Of Recurrencementioning
confidence: 99%
“…The precise underlying pathophysiology of LA remodelling is also not entirely clear but include local and systemic inflammation, atrial fibrosis, atrial enlargement, altered autonomic tone, and anatomical and electrical changes [17,18]. Such structural changes and fibrosis increase the surface for multiple wave propagation, causing AF both to emerge and become more persistent [19].…”
Section: Atrial Size and Volumementioning
confidence: 99%